Do Vertical Contracts Lead to Foreclosure and Efficiency Gains? An Empirical Study of the Food and Beverage Industry - Bertarelli, Silvia (European Scientific Journal, ESJ, 2024)
This paper focuses on presenting a research methodology to determine whether vertical contracts between firms operating at different levels of the supply chain are efficient from the perspective of recent industrial organisation theory. In this perspective, some case studies were presented concerning antitrust investigations against some large companies operating in the food and beverage sector in Italy. Despite the controversy surrounding the effects of vertical agreements, as they may be pro- or anti-competitive, the paper shows that not only market concentration but also intra-sectoral asymmetries are crucial factors to consider in distinguishing between foreclosing and efficiency-enhancing agreements.